The Relationship Between Parental Psychological Control and College Students’ Non-Suicidal Self-Injury: The Chain Mediation Roles of Relative Deprivation and Depression and the Moderating Role of Peer Relationships - Sachula Cui; Qiang Bao (Behavioral Sciences, 2025)
Previous research has demonstrated that parental psychological control increases the likelihood of non-suicidal self-injury (NSSI) among college students. However, the underlying mechanisms of this association remain unclear. This study aims to investigate whether relative deprivation and depression serve as chain mediators in the relationship between paternal/maternal psychological control and NSSI, while also examining the moderating role of peer relationships. A total of 1158 college students (48.3% female; Mage = 19.26 years) completed assessments measuring parental psychological control, relative deprivation, depression, peer relationships, and NSSI. The results revealed that both paternal and maternal psychological control influence college students’ NSSI through two distinct pathways: the mediating role of depression, and a chain-mediating pathway involving relative deprivation followed by depression. Peer relationships moderated multiple associations, including those between paternal psychological control and NSSI, paternal psychological control and depression, relative deprivation and NSSI, and depression and NSSI. Notably, positive peer relationships helped mitigate the adverse effects stemming from paternal psychological control. However, peer relationships failed to buffer the negative impacts induced by maternal psychological control. These findings provide nuanced insights into the differential mechanisms through which paternal versus maternal psychological control influences college students’ NSSI. The results emphasize the necessity for distinct prevention and intervention strategies tailored to address the unique effects of paternal and maternal psychological control, thereby assisting practitioners in developing targeted approaches to reduce NSSI among college students.